Inovasi dan Analisis Kebutuhan Sistem Informasi untuk Smart Irrigation - Nasir, Januardi; Setiawan, Yasha Langitta (PUAN INDONESIA, 2025)
Agriculture plays an important role in the economic structure of Agam Regency, where the majority of the population relies on agriculture as their main source of income. A well-functioning irrigation system is essential to support this agricultural sector, and its optimal management is essential. Inadequate irrigation management can have various negative impacts, including the conversion of agricultural land into empty or unproductive land, which then impacts regional income and the welfare of local farmers. This study emphasizes how irrigation assets are managed in Agam Regency and the obstacles encountered. In a region that is predominantly dependent on agriculture, approximately 70% of the land is used for agriculture, including 885 irrigation sites that require efficient management and rehabilitation, often carried out by authorities together with farmer groups. This research focuses on answering the urgent need for an integrated information system for irrigation management in Agam Regency. It is aspiring to develop a roadmap for implementing smart irrigation through information systems. Furthermore, practical investigations will develop information systems to facilitate decision-making processes in better irrigation management. The research methodology uses a qualitative descriptive method, which involves collecting data through questionnaires and interviews with relevant stakeholders, parties from government and farmer groups. Data will be processed using descriptive statistical analysis, focusing on the main problems identified during the research. Result of this study as a basic step towards developing an integrated information system for smart irrigation management in Agam Regency, which aims to improve agricultural sustainability, increase income and resource efficiency..